Point‐of‐care echocardiography of the right heart improves acute heart failure risk stratification for low‐risk patients: The REED‐AHF prospective study. (26th September 2022) - Harrison, Nicholas E.; Favot, Mark J.; Gowland, Laura; Lenning, Jacob; Henry, Sarah; Gupta, Sushane; Abidov, Aiden; Levy, Phillip; Ehrman, Robert
Abstract: Objectives: Validated acute heart failure (AHF) clinical decision instruments (CDI) insufficiently identify low‐risk patients meriting consideration of outpatient treatment. While pilot data show that tricuspid annulus plane systolic excursion (TAPSE) is associated with adverse events, no AHF CDI currently incorporates point‐of‐care echocardiography (POCecho). We evaluated whether TAPSE adds incremental risk stratification value to an existing CDI. Methods: Prospectively enrolled patients at two urban‐academic EDs had POCechos obtained before or <1 h after first intravenous diuresis, positive pressure ventilation, and/or nitroglycerin. STEMI and cardiogenic shock were excluded. AHF diagnosis was adjudicated by double‐blind expert review. TAPSE, with an a priori cutoff of ≥17 mm, was our primary measure. Secondary measures included eight additional right heart and six left heart POCecho parameters. STRATIFY is a validated CDI predicting 30‐day death/cardiopulmonary resuscitation, mechanical cardiac support, intubation, new/emergent dialysis, and acute myocardial infarction or coronary revascularization in ED AHF patients. Full (STRATIFY + POCecho variable) and reduced (STRATIFY alone) logistic regression models were fit to calculate adjusted odds ratios (aOR), category‐free net reclassification index (NRIcont ), ΔSensitivity (NRIevents ), and ΔSpecificity (NRInonevents ). Random forest assessed variable importance. To benchmark risk prediction to standard of care, ΔSensitivity and ΔSpecificity were evaluated at risk thresholds more conservative/lower than the actual outcome rate in discharged patients. Results: A total of 84/120 enrolled patients met inclusion and diagnostic adjudication criteria. Nineteen percent experiencing the primary outcome had higher STRATIFY scores compared to those event free (233 vs. 212, p = 0.009). Five right heart (TAPSE, TAPSE/PASP, TAPSE/RVDD, RV‐FAC, fwRVLS) and no left heart measures improved prediction ( p < 0.05) adjusted for STRATIFY. Right heart measures also had higher variable importance. TAPSE ≥ 17 mm plus STRATIFY improved prediction versus STRATIFY alone (aOR 0.24, 95% confidence interval [CI] 0.06–0.91; NRIcont 0.71, 95% CI 0.22–1.19), and specificity improved by 6%–32% ( p < 0.05) at risk thresholds more conservative than the standard‐of‐care benchmark without missing any additional events. Conclusions: TAPSE increased detection of low‐risk AHF patients, after use of a validated CDI, at risk thresholds more conservative than standard of care.